Citarum Harum Project: A Restoration Model of River Basin - Abdul Malik Sadat Idris; Angga Sukmara Christian Permadi; Aozora Insan Kamil; Bintang Rahmat Wananda; Aditya Riski Taufani (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2019)
‘Citarum Harum’ is a program to restore the Citarum River. The problem of waste and sewage and the existence of the strategic Citarum River by splitting West Java Province are very supportive of economic growth, especially labour-intensive industries that can absorb a lot of labour into serious problems. Citarum, which is known as one of the dirtiest rivers in the world, urges the government to immediately issue regulations to start the restoration of the Citarum River Basin (DAS Citarum). Citarum watershed pollution and damage mitigation measures in an integrated strategic pace for control and law enforcement that integrate authority between government agencies and stakeholders related to Citarum watershed recovery based on Presidential Regulation No. 15 of 2018 concerning Acceleration of Pollution and Damage Control in the Citarum River Basin. Various steps and methods were taken to restore the Citarum watershed, as well as communication and coordination of the central government with various related parties such as the Environmental Service Office (DLH) of the West Java Provincial Government and Kodam III Siliwangi to be enhanced to immediately realize Harum Citarum.